Effects of Oral Carotenoids on Oxidative Stress: A Systematic Review and Meta-Analysis of Studies in the Recent 20 Years - Zhuang, Chengfei; Yuan, Jinping; Du, Yimei; Zeng, Jing; Sun, Yan; Wu, Yan; Gao, Xing-Hua; Chen, Hong-Duo (Frontiers in Nutrition, 2022)
Carotenoids protect organs, tissues and cells from damaging action of singlet oxygen, oxygen radicals and lipid peroxides. This systematic review was sought to evaluate the influence of oral carotenoids on anti-oxidant/oxidative markers, blood carotenoids levels, and lipid/lipoprotein parameters in human subjects. A comprehensive review of relevant literatures was conducted in PubMed, Web of Sciences and the Cochrane library, from 2000 to December 2020. Randomized controlled trials, case-controlled trials or controlled trials were identified. Eighteen trials were included, with the target populations being healthy subjects in 16 studies, athletes in 1 study, and pregnancy women in 1 study. The meta-analysis results showed that carotenoids complex supplementation significantly increased the levels of antioxidative parameters FRAP and ORAC (SMD=0.468; 95%CI: 0.159 to 0.776, p=0.003; SMD= 0.568; 95%CI: 0.190 to 0.947, p=0.003), and decreased the blood TG level (SMD= -0.410, 95%CI: -0.698 to -0.122, p=0.005). Oral carotenoids supplement significantly increased the blood levels of β-carotene (SMD=0.490, 95%CI: 0.123 to 0.858, p=0.009), α-tocopherol (SMD=0.752, 95%CI: 0.020 to 1.485, p=0.044), and the intaking durations were 8 weeks. The levels of antioxidative enzymes and other lipid/lipoprotein parameters were not different between subjects receiving carotenoids and controls (p>0.05). In conclusion, our systematic review showed that carotenoids complex is beneficial for alleviating potential oxidative stress via interacting with free radical or decreasing blood TG level. The intaking duration of carotenoids should be 8 weeks to reach an enough concentration for function.